Risk Scores Based on Six Survival-Related RNAs in a Competing Endogenous Network Composed of Differentially Expressed RNAs Between Clear Cell Renal Cell Carcinoma Patients Carrying Wild-Type or Mutant Von Hippel–Lindau Serve Well to Predict Malignancy and Prognosis - Zhu, Rui; Li, Xiezhao; Cai, Zhiduan; Liang, Siyang; Yuan, Yaoji; Xu, Yuyu; Lai, Dehui; Zhao, Haibo; Yang, Weiqing; Bian, Jun; Liu, Leyuan; Xu, Guibin (Frontiers in Oncology, 2021)
Clear cell renal cell carcinomas (ccRCC) patients carrying wild type Von Hippel-Lindau Tumor Suppressor (VHL) are more invasive and of high morbidity. Concurrently, competitive endogenous RNA (ceRNA) network has been suggested to play an important role in ccRCC malignancy. In order to understand why the patients carrying wild type VHL gene have high degrees of invasion and morbidity, we applied bioinformatics approaches to identify 861 differently expressed RNAs (DE-RNAs) between patients carrying wild-type and patients carrying mutant VHL from TCGA database, established a ceRNA network including 122 RNAs, and elected six survival-related DE-RNAs including Linc00942, Linc00858, RP13_392I16.1, hsa-miR-182-5p, hsa-miR-183-5p and PAX3. Examining clinical samples from our hospital revealed that patients carrying wild type VHL had significantly higher levels of all six RNAs than those carrying mutant VHL. Patients carrying wild type VHL had significantly higher risk scores which were calculated based on expression levels of all six RNAs than those carrying mutant VHL. Patients with higher risk scores had significantly shorter survival times than those with lower risk scores. Therefore, the risk scores serve well to predict malignancy and prognosis.